Polar auxin transport is essential to maintain growth and development of etiolated pea and maize seedlings grown under 1 g conditions: Relevance to the international space station experiment. (February 2019) - Miyamoto, Kensuke; Inui, Akinori; Uheda, Eiji; Oka, Mariko; Kamada, Motoshi; Yamazaki, Chiaki; Shimazu, Toru; Kasahara, Haruo; Sano, Hiromi; Suzuki, Tomomi; Higashibata, Akira; Ueda, Junichi
Abstract: We conducted "Auxin Transport" space experiments in 2016 and 2017 in the Japanese Experiment Module (JEM) on the International Space Station (ISS), with the principal objective being integrated analyses of the growth and development of etiolated pea ( Pisum sativum L. cv Alaska) and maize ( Zea mays L. cv Golden Cross Bantam) seedlings under true microgravity conditions in space relative to auxin dynamics. Etiolated pea seedlings grown under microgravity conditions in space for 3 days showed automorphogenesis. Epicotyls and roots bent ca. 45° and 20° toward the direction away from the cotyledons, respectively, whereas those grown under artificial 1 g conditions produced by a centrifuge in the Cell Biology Experimental Facility (CBEF) in space showed negative and positive gravitropic response in epicotyls and in roots, respectively. On the other hand, the coleoptiles of 4-day-old etiolated maize seedlings grew almost straight, but the mesocotyls curved and grew toward a random direction under microgravity conditions in space. In contrast, the coleoptiles and mesocotyls of etiolated maize seedlings grown under 1 g conditions on Earth were almost straight and grew upward or toward the direction against the gravity vector. The polar auxin transport activity in etiolated pea epicotyls and in maize shoots was significantly inhibited and enhanced, respectively, under microgravity conditions in space as compared with artificial 1 g conditions in space or 1 g conditions on Earth. An inhibitor of polar auxin transport, 2, 3, 5-triiodobenzoic acid (TIBA) substantially affected the growth direction and polar auxin transport activity in etiolated pea seedlings grown under both artificial 1 g and microgravity conditions in space. These results strongly suggest that adequate polar auxin transport is essential for gravitropic response in plants. Possible mechanisms enhancing polar auxin transport in etiolated maize seedlings grown under microgravity conditions in space are also proposed.